Agronomic performance of Conilon coffee clones in the humid subtropical climate of Registro, Vale do Ribeira, SP, Brazil - Oliveira, Marilia da Silva Borba [UNESP]; Carvalho, Alex Mendonca de [UNESP]; Godoy, Leandro Jose Grava de [UNESP]; Ferrari, Samuel [UNESP]; Gardino, Gabriel Nunes [UNESP]; Teramoto, Erico Tadao [UNESP] (Univ Federal Mato Grosso, 2024)
Coffee, a globally traded and profitable commodity, is pivotal in many countries' economies and social development. In the Vale do Ribeira, a region of significant socio-environmental importance, coffee farming has the potential to boost local family agriculture through the diversification of agricultural production, with a focus on Conilon coffee ( Coffea canephora Pierre), which thrives in hot and humid climates. In this context, our study's in situ evaluation of the agronomic performance of Conilon coffee clones is of utmost importance. We assessed the vegetative growth, incidence of pests and diseases, productivity, and grain ripening of various Conilon coffee clones in Registro, located in the humid subtropical environment of Vale do Ribeira. Clones 401 and 410 demonstrated superior vegetative growth. Pests and diseases, such as leaf miner, Phoma, and Cercosporiosis, were more prevalent during higher temperatures, while rust was a concern in cooler temperatures. The most productive clones were 13V, 407, 403, and 409, with a higher percentage of grains in the cherry stage, making them the most promising for cultivation in the region.
Keywords: brown eye spot; leaf miner; Mata Atl & acirc;ntica; plant growth; yield